Proceedings of the Annual Symposium on Computer-Human Interaction in Play 2020
DOI: 10.1145/3410404.3414235
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Game Difficulty and Churn Without Players

Abstract: Figure 1: Scatter plots depicting the relation of pass rate (a measure of level difficulty) and churn rate over 168 game levels of Angry Birds Dream Blast, in both real player data and our simulations. Here, churn is defined as not playing for 7 days. The colors denote level numbers. The baseline simulation model predicts pass rate and churn directly from AI gameplay. Our proposed extended model augments this with a simulation of how the player population evolves over the levels.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 88 publications
(102 reference statements)
1
36
0
Order By: Relevance
“…It is important to acknowledge that the measurement of subjective experience through self-reported survey scales is only one of several research methods used at CHI PLAY. For example, and this is by no means exhaustive, player behavior and experience is also explored using qualitative methods such as grounded theory [9] and ethnomethodologyinformed ethnography [49] or with AI agents in simulations [42]. Indeed, when submitting a paper to the CHI PLAY conference, authors are able to choose from many different contributions beyond research which involves the quantitative measurement of constructs [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to acknowledge that the measurement of subjective experience through self-reported survey scales is only one of several research methods used at CHI PLAY. For example, and this is by no means exhaustive, player behavior and experience is also explored using qualitative methods such as grounded theory [9] and ethnomethodologyinformed ethnography [49] or with AI agents in simulations [42]. Indeed, when submitting a paper to the CHI PLAY conference, authors are able to choose from many different contributions beyond research which involves the quantitative measurement of constructs [2].…”
Section: Introductionmentioning
confidence: 99%
“…We account for the complexity of engagement as player experience [8] by operationalizing it in terms of player churn, which can be triggered by any of the underlying factors [38]. Existing computational work has considered the churn probability of an individual player [6,47], or the average churn rate measured over a population of players and a part of the game such as a single game level [45,46]. Predicting the churn probability of a particular player allows game developers to offer personalized incentives to continue playing.…”
Section: Operationalizing Engagement and Difficultymentioning
confidence: 99%
“…In their specific study, they found that the number of moves a DRL agent needs for completing a level has the highest correlation with human player pass rates if one uses the maximum found among the top 5% best runs. As part of the second extension contributed in this paper, we test their hypothesis by modifying the AI gameplay features used in our previous approach [46] (see RQ2).…”
Section: Operationalizing Engagement and Difficultymentioning
confidence: 99%
See 2 more Smart Citations